Sheet Metal 2013 - Leacock, Alan G.; Duflou, Joost R.; Merklein, Marion; Micari, Fabrizio; et al. (Trans Tech Publication, 2013)
The collection provides an outlet for both industry and academia alike to present their latest findings in the area of sheet metal forming. Volume is indexed by Thomson Reuters CPCI-S (WoS). There are 69 peer reviewed contributions from Industry and academia representing 23 Countries. The research presented covers a diverse field from the fundamental testing and characterisation of sheet metals to the development of new and innovative forming processe